Carbon-based material as well as preparation method and application thereof

Through the carbon-based material modified by electron shuttle, the problem that the existing technology cannot effectively activate mineral elements in the soil is solved, the efficient reduction and dissolution of soil minerals and the activation of mineral elements is achieved, the soil nutrition is improved, and the healthy growth of plants is achieved. Provide guarantees.

CN119432385AActive Publication Date: 2025-02-14GUANGDONG INST OF ECO ENVIRONMENT & SOIL SCI

Patent Information

Application Number
CN202411674863.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-14
Estimated Expiration
2044-11-21

AI Technical Summary

Technical Problem

The prior art cannot effectively activate mineral nutrients fixed in minerals, resulting in a decrease in soil nutrition and affecting plant growth and human health.

Method used

The surface modification of lignin is performed through electron shuttle body, and the electron shuttle body fragment is introduced on the surface of lignin by chemical synthesis to prepare a carbon-based material with high electron shuttle capacity. This material can promote the reduction and dissolution of soil minerals and activate mineral elements.

Benefits of technology

It realizes efficient reduction and dissolution of soil minerals, activates mineral elements, improves soil nutrition, provides guarantee for the healthy growth of plants, and has the advantages of low-cost, easy-to-get raw materials, and good stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005146768890000041
    Figure BDA0005146768890000041
  • Figure BDA0005146768890000051
    Figure BDA0005146768890000051
  • Figure HDA0005146768900000011
    Figure HDA0005146768900000011
Patent Text Reader

Abstract

The invention relates to the technical field of soil improvement, and discloses a carbon-based material as well as a preparation method and application thereof. The carbon-based material is electron shuttle modified lignin. According to the carbon-based material provided by the invention, the lignin is subjected to surface modification by using the electron shuttle, the lignin is rich in resource, easily available in raw material, low in cost, good in stability and harmless, and high electron shuttle activity fragments are introduced on the surface by combining with the electron shuttle, so that the electron shuttle capability is greatly improved; the carbon-based material has the capability of promoting reduction and dissolution of soil minerals, and can be applied to soil improvement, improvement of electron transfer rate between microorganisms and minerals, acceleration of mineral dissolution and activation of soil mineral elements, effective regulation and control of soil iron circulation process so as to improve soil trophism, and guarantee for healthy growth of plants. Compared with a small-molecule shuttle, the shuttle is not easy to deteriorate or lose in the environment, can play a role in soil for a long time, and has great application potential for carbon sequestration and quality improvement of soil and guarantee of crop nutrition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of soil improvement, and in particular to a carbon-based material and a preparation method and application thereof. Background Art

[0002] Plants need to take in a variety of trace nutrients from the soil during their growth period. Insufficient intake or imbalance of nutrients will lead to large-scale yield reduction and crop quality decline. Long-term intake of low-quality crops by humans can easily lead to health problems such as mental retardation, loss of labor ability, and decreased immunity. Large-scale crop yield reduction will also cause huge direct economic losses. Therefore, activating soil mineral elements, improving soil quality, and meeting the intake needs of plant growth are of great significance to protecting human health and economic development.

[0003] CN 114958384A discloses a method for activating soil using mineral enzymes. After the minerals are pretreated, fermented, dried, and piled, a high-activity mineral enzyme treatment agent is obtained. The high-activity mineral enzyme treatment agent is used to activate the soil to solve the problem of soil degradation. However, the technology requires more processes, and after the minerals are added to the soil, the metals therein may have a negative effect on the environment. CN 107082716A discloses a value-added urea that can activate the soil and a preparation method thereof. The value-added urea is synthesized from urea, highly active organic matter, a chelating agent, and trace elements in an oxidized state, and is used to inhibit the generation of ammonium nitrogen and nitrate nitrogen in the soil and improve the utilization rate of fertilizers. The urea used in the technology is relatively expensive and needs to be synthesized under high temperature conditions, and the operating conditions are relatively harsh. In addition, the above-mentioned technologies are unable to activate the mineral nutrients fixed in the minerals for absorption by crops. Summary of the invention

[0004] The present invention aims to solve at least one of the above-mentioned technical problems existing in the prior art. To this end, one of the purposes of the present invention is to provide a carbon-based material; the second purpose of the present invention is to provide a method for preparing the carbon-based material; the third purpose of the present invention is to provide an application of the carbon-based material.

[0005] The basic principle of the present invention is described as follows:

[0006] Lignin is widely present in plants and is abundant in resources. It can be purchased commercially. The active functional groups (hydroxyl groups) contained on its surface have certain reactivity. The present invention uses an electron shuttle to modify the surface of lignin. The two are combined by bonding by chemical synthesis, and electron shuttle fragments are introduced on the surface of lignin to give lignin electron shuttle ability.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is:

[0008] A first aspect of the present invention provides a carbon-based material, wherein the carbon-based material is lignin modified by an electron shuttle.

[0009] Preferably, the mass ratio of the electron shuttle to lignin is 1:(0.5-25); further preferably, the mass ratio of the electron shuttle to lignin is 1:(0.7-20).

[0010] Preferably, the electron shuttle is an anthraquinone compound; further preferably, the electron shuttle is anthraquinone-2-carboxylic acid.

[0011] Specifically, anthraquinone-2-carboxylic acid, as a typical electron shuttle, can be obtained through commercial purchase, and the raw material is easily available.

[0012] Preferably, the lignin comprises guaiacyl lignin (G type).

[0013] Specifically, lignin contains abundant functional groups, including functional groups on the benzene ring (methoxy and phenolic hydroxyl) and functional groups on the side chain structure (alcoholic hydroxyl, carbonyl, carboxyl and double bond structure). These functional groups will significantly affect the reaction characteristics of lignin. The methoxy group is an important group that distinguishes lignin units and has strong stability. It requires a strong oxidant to cleave from the benzene ring structure. There are many methoxy substituents on the benzene ring and the steric hindrance is large, which will limit the coupling mode between units. There is no methoxy functional group at the C5 position of the G-type lignin unit, so a variety of coupling reactions can occur.

[0014] Preferably, the carbon-based material comprises the following preparation raw materials: lignin, an electron shuttle, a solvent, a catalyst and a dehydrating agent.

[0015] Preferably, the mass ratio of the lignin, the catalyst and the dehydrating agent is 1000:(2-60):(40-800); further preferably, the mass ratio of the lignin, the catalyst and the dehydrating agent is 1000:(2.4-50):(40-750).

[0016] Preferably, the catalyst comprises 4-dimethylaminopyridine (DMAP).

[0017] Preferably, the dehydrating agent comprises dicyclohexylcarbodiimide (DCC).

[0018] Preferably, the solvent comprises C1-C2 chloroalkane; further preferably, the solvent comprises dichloromethane (DCM).

[0019] The second aspect of the present invention provides a method for preparing the carbon-based material according to the first aspect of the present invention, comprising the following steps:

[0020] S1. Add lignin and electron shuttle into a reaction device, introduce inert gas, add solvent, and obtain a mixed solution;

[0021] S2. Mix the catalyst, dehydrating agent and solvent, add them into the mixed liquid, react and obtain the carbon-based material.

[0022] Preferably, in step S1, the solid-liquid ratio of the lignin to the solvent is 1 g:(2-30) mL; further preferably, the solid-liquid ratio of the lignin to the solvent is 1 g:(2.5-25) mL.

[0023] Preferably, in step S1, the inert gas includes nitrogen.

[0024] Preferably, in the step S1, the adding of the solvent is followed by stirring.

[0025] Preferably, the stirring time is 10-20 min; more preferably, the stirring time is 10-15 min.

[0026] Preferably, in step S2, the solid-liquid ratio of the catalyst to the solvent is (0.2-10) mg:1 mL; further preferably, the solid-liquid ratio of the catalyst to the solvent is (0.24-10) mg:1 mL.

[0027] Preferably, in step S2, the reaction time is 24-96 hours; further preferably, the reaction time is 40-80 hours.

[0028] Preferably, in step S2, after the reaction is completed, the steps of filtering, washing and drying are also included.

[0029] The third aspect of the present invention provides the use of the carbon-based material described in the first aspect of the present invention in soil improvement.

[0030] Preferably, the soil improvement is reduction and activation of mineral elements in the soil.

[0031] Preferably, the mineral elements include iron, selenium, zinc and calcium.

[0032] Preferably, the amount of the carbon-based material used is (0.1-1.5) g / kg soil; further preferably, the amount of the carbon-based material used is (0.1-1) g / kg soil.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] 1) The carbon-based material provided by the present invention uses an electron shuttle to modify the surface of lignin. Lignin resources are abundant, the raw materials are easily available, the cost is low, the stability is good and it is harmless. By combining with the electron shuttle to introduce high electron shuttle activity fragments on the surface, the electron shuttle ability is greatly improved, so that the carbon-based material has the ability to promote the reduction and dissolution of soil minerals;

[0035] 2) The method for preparing the carbon-based material provided by the present invention has simple steps, mild process conditions, can be carried out at room temperature, has low energy consumption, is easy to promote and use, and realizes large-scale industrial production;

[0036] 3) The carbon-based material provided by the present invention has the ability to promote the reduction and dissolution of soil minerals, can be used for soil improvement, increase the electron transfer rate between microorganisms and minerals, accelerate mineral dissolution and activation of soil mineral elements, effectively regulate the soil iron cycle process to improve soil nutrition, and provide protection for the healthy growth of plants; compared with small molecule shuttles, the carbon-based material is not easy to deteriorate or lose in the environment, can play a role in the soil for a long time, and has great application potential for soil carbon fixation and quality improvement and ensuring the nutrition of crops. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 is the infrared spectrum of the carbon-based material 1 in Example 1;

[0038] Figure 2 is the hydrogen nuclear magnetic resonance spectrum of the carbon-based material 1 in Example 1;

[0039] Figure 3 This is an enlarged view of the 7.60-9.00 ppm range of the hydrogen nuclear magnetic resonance spectrum of the carbon-based material 1 in Example 1;

[0040] Figure 4 is a scanning electron microscope image of the carbon-based material 1 in Example 1;

[0041] Figure 5 This is the kinetic curve of the generation of Fe(II) in the hydrochloric acid extractable state in the reduction stage of Experimental Example 1;

[0042] Figure 6 This is the kinetic curve of the generation of Fe(II) in the hydrochloric acid extractable state in the reduction stage of Experimental Example 2;

[0043] Figure 7 The kinetic curve of Fe(II) extracted by hydrochloric acid in the reduction stage in Experimental Example 3;

[0044] Figure 8 This is the kinetic curve of DOC in the reduction stage in Experimental Example 3. DETAILED DESCRIPTION

[0045] The present invention is further described in detail below by specific examples. The raw materials, reagents or devices used in the examples can be obtained from conventional commercial sources or by prior art methods unless otherwise specified. Unless otherwise specified, the experiments or test methods are conventional methods in the art.

[0046] The lignin used in the following examples was purchased from Sichuan Weiqi Biotechnology Co., Ltd.;

[0047] The strain used for mineral reduction in the test example was Shewanella MR-1, purchased from the Marine Microbial Culture Collection (MCCC), with the collection number LMG 19005, and was preserved in 25% glycerol (v / v) before use and stored in a -80°C refrigerator;

[0048] The soil samples used in the rice pot experiment in the test example were paddy field soil (soil surface depth 0-20 cm) collected from Jiangmen City, Guangdong Province. The soil samples were naturally air-dried at room temperature in a dry and cool place in the laboratory. After impurities were removed, they were ground through a 2 mm sieve and stored in a plastic container before chemical analysis.

[0049] The synthetic route for preparing the carbon-based material in the embodiment is shown as follows:

[0050]

[0051] Example 1

[0052] This embodiment prepares a carbon-based material, and the steps are as follows:

[0053] S11, a magnetic stirrer, 2.0 g of lignin, and 750 mg (3.0 mmol) of anthraquinone-2-carboxylic acid were added to a 100 mL Schlenk bottle, and nitrogen was replaced three times. 30 mL of anhydrous dichloromethane was added to the Schlenk bottle, and the mixture was stirred on a magnetic stirrer for 10 min at room temperature to obtain a mixed solution;

[0054] S21. Dissolve 36 mg of 4-dimethylaminopyridine and 681 mg of dicyclohexylcarbodiimide in 20 mL of dichloromethane, and add the mixture dropwise to the mixed solution obtained in step S11. Stir at room temperature for 48 h. Complete conversion of anthraquinone-2-carboxylic acid is detected by thin layer chromatography. Filter, wash the filter cake with dichloromethane, and dry to obtain carbon-based material 1.

[0055] Example 2

[0056] This embodiment prepares a carbon-based material, and the steps are as follows:

[0057] S11, add a magnetic stirrer, 2.0 g of lignin, and 1.25 g (5.0 mmol) of anthraquinone-2-carboxylic acid to a 100 mL Schlenk bottle, replace nitrogen three times, add 30 mL of anhydrous dichloromethane to the Schlenk bottle, place it on a magnetic stirrer and stir for 10 min at room temperature to obtain a mixed solution;

[0058] S21. Dissolve 60 mg of 4-dimethylaminopyridine and 1.14 g of dicyclohexylcarbodiimide in 20 mL of dichloromethane, and add the mixture dropwise to the mixed solution obtained in step S11. Stir at room temperature for 72 h. Complete conversion of anthraquinone-2-carboxylic acid is detected by thin layer chromatography. Filter, wash the filter cake with dichloromethane, and dry to obtain carbon-based material 2.

[0059] Material characterization

[0060] 1. Perform infrared spectroscopy test on the carbon-based material 1 prepared in Example 1:

[0061] Figure 1 is the infrared spectrum of the carbon-based material 1 in Example 1, Figure 1 It can be seen that at 1676cm -1 The characteristic peak of quinone group appeared at , indicating that anthraquinone-2-carboxylic acid was successfully coupled with lignin.

[0062] 2. Using deuterated methanol as solvent, the carbon-based material 1 prepared in Example 1 was tested by nuclear magnetic resonance hydrogen spectrum:

[0063] Figure 2 is the hydrogen nuclear magnetic resonance spectrum of the carbon-based material 1 in Example 1, Figure 3 This is an enlarged view of the 7.60-9.00 ppm range of the nuclear magnetic resonance hydrogen spectrum of the carbon-based material 1 in Example 1. Figure 2 and Figure 3 It can be seen that in the nuclear magnetic resonance hydrogen spectrum of the carbon-based material 1, the characteristic peak of anthraquinone aromatic hydrogen appears in the hydrogen spectrum chemistry range of 7.60-9.00 ppm, indicating that anthraquinone-2-carboxylic acid is successfully coupled with lignin.

[0064] 3. The carbon-based material 1 prepared in Example 1 was tested by scanning electron microscopy:

[0065] Figure 4 is a scanning electron microscope image of the carbon-based material 1 in Example 1, Figure 4 It can be seen that by modifying lignin with anthraquinone-2-carboxylic acid, highly electron shuttling active fragments are formed on the surface, which is beneficial to improving the electron shuttling ability of lignin materials.

[0066] Test example

[0067] Test preparation and measurement methods:

[0068] 1. Synthesis and calibration of ferrihydrite

[0069] Accurately weigh 8 g of ferric nitrate nonahydrate (Fe(NO 3 ) 3 9H 2 O), add 100mL ultrapure water and dissolve it in a beaker. Then prepare 150mL 1mol / L sodium hydroxide solution. In 5min, the sodium hydroxide solution is added dropwise to the ferric nitrate solution, and the pH of the mixed solution is neutralized to 7.5. The process is always kept by an electric stirrer to mix the solution vigorously. After the pH is stabilized at 7.5 and reaches 8h, a suspension of dilinear ferrihydrite is obtained. The suspension is centrifuged and washed with deionized water for more than three times to remove excess electrolyte in the suspension. The washed suspension is finally resuspended with 100mL deionized water to obtain a ferrihydrite suspension, which can be stored in a 4°C refrigerator for three days.

[0070] The concentration of iron minerals in the suspension needs to be calibrated to ensure the uniformity of the mineral concentration in the reaction system. Specifically, the prepared ferrihydrite suspension is ultrasonicated for 1 h, and a 2 mL centrifuge tube is taken and its mass is accurately weighed and recorded as m 1 , transfer 2 mL of ferrihydrite suspension to this centrifuge tube for freeze drying, and record its volume as v. The mass of the centrifuge tube and the iron ore after drying is recorded as m. 2 , the concentration c of the ferrihydrite suspension is obtained by the difference calculation method. The calculation formula is as follows:

[0071]

[0072] 2. Microbial activation culture

[0073] (1) Prepare the culture medium required for microbial activation culture. The nutrient composition of the culture medium is as follows (1.0 L): 10 g tryptone, 5 g yeast extract and 10 g sodium chloride. After preparation, adjust the pH of the culture medium to 7.0 using hydrochloric acid and sodium hydroxide. Dispense the culture medium into 250 mL conical flasks, add 100 mL of culture medium to each flask, and sterilize the culture medium using a high-temperature and high-pressure sterilizer.

[0074] (2) Take the MR-1 strain out of the -80℃ freezer and quickly thaw it on ice. Make sure the tube is thawed on ice to avoid prolonged exposure to room temperature. After the bacterial solution begins to melt, use a sterile inoculation loop to dip a small amount of bacterial solution in a sterile operating table and inoculate it into a conical flask containing 100mL of culture medium. Then, place the conical flask in a constant temperature shaking box at 30℃ and 180rpm for about 12-16 hours to promote the bacteria to enter the logarithmic growth phase.

[0075] (3) Prepare LB solid culture medium with the following nutrient composition (1.0L): 15g agar, 10g tryptone, 5g yeast extract and 10g sodium chloride, and sterilize it as well. After sterilization, cool the culture medium to about 50°C, pour it into a sterile culture dish on a sterile operating table, and wait for it to solidify into a solid. When the bacteria in the liquid culture medium have obvious growth, inoculate it into the solid culture medium on a sterile operating table (plate streak method), place the culture dish in a 30°C biochemical incubator, and culture it in the dark for 20 hours. Then put the plate in a 4°C refrigerator for storage, which can be stored for 1 week. Pick a single MR-1 colony with a sterile inoculation loop on a sterile operating table and inoculate it into a conical flask containing 100mL of culture medium, and culture it under constant temperature shaking conditions (30°C, 180rpm) until the logarithmic growth phase, about 12-16 hours. The cultured bacterial suspension was centrifuged to obtain bacterial precipitate, and the centrifuged bacterial suspension was washed 3-4 times with piperazine-1,4-diethanesulfonic acid (PIPES) buffer at pH 7.0. Finally, the washed bacterial suspension was dispersed in PIPES buffer, shaken, and the OD of the bacterial suspension was adjusted. 600 To 0.1.

[0076] 3. Extraction and determination of ferrous iron

[0077] Shake the sample in the vial, pipette 0.2 mL of sample suspension into 0.2 mL of hydrochloric acid, and extract at a rate of 180 rpm for 60 min at room temperature in the dark. After the extraction, centrifuge, pipette 0.2 mL of supernatant, add 0.4 mL of sodium acetate buffer and 0.1 mL of o-phenanthroline color developer, and color in the dark for 10 min. Then, measure the absorbance of the sample at a wavelength of 510 nm, and calculate the actual concentration of ferrous iron in the sample based on the ferrous iron mark.

[0078] Test Example 1

[0079] Add 50mL of experimental solution to a 100mL vial to construct a microcosm culture system. The experimental solution includes: PIPES buffer, ferrihydrite suspension and sodium lactate. The concentration of the ferrihydrite suspension is 200mg / L, and the concentration of sodium lactate is 5mmol / L. The carbon-based material 1 prepared in Example 1 was added to the vial of the experimental group, and only bacterial solution was added to the control group. The concentration of carbon-based material 1 in the experimental group was 0.8g / L, and the initial content of microorganisms was about 10 7 The protein content was used as the benchmark to ensure that the initial concentration of the experimental group and the control group was consistent. The control group and the experimental group were cultured in a constant temperature shaking box at 30°C and 180 rpm, and the ferrous iron concentration was measured at 0, 6, 12, 24, 48, 72 and 96 hours of the reaction.

[0080] Figure 5 is the kinetic curve of the generation of Fe(II) in the hydrochloric acid extraction state in the reduction stage of Experimental Example 1, Figure 5 It can be seen that in the control group with only added bacteria, the reduction rate of ferrihydrite is slow, the content of ferrous iron extracted by hydrochloric acid tends to balance after 48 hours of reaction, and the content of ferrous iron extracted by hydrochloric acid is only 60.78 mg / L after 96 hours of reaction, accounting for only 30.39% of the total amount of ferrihydrite. In the test group with added carbon-based material 1, the reduction rate of ferrihydrite is fast, the content of ferrous iron extracted by hydrochloric acid tends to balance after 6 hours of reaction, and the content of ferrous iron extracted by hydrochloric acid is 69.78 mg / L after 96 hours of reaction, accounting for 34.89% of the total amount of ferrihydrite. The results of the kinetic experiment show that the reduction rate of ferrihydrite is significantly different in the test group with added carbon-based material 1 and the control group with only added bacterial solution, and carbon-based material 1 can effectively promote the reduction process of ferrihydrite.

[0081] Test Example 2

[0082] Add 50mL of experimental solution to a 100mL vial to construct a microcosm culture system. The experimental solution includes: PIPES buffer, ferrihydrite suspension and sodium lactate. The concentration of the ferrihydrite suspension is 200mg / L, and the concentration of sodium lactate is 5mmol / L. The carbon-based material 2 prepared in Example 2 was added to the vial of the experimental group, and only bacterial solution was added to the control group. The concentration of carbon-based material 2 in the experimental group was 0.8g / L, and the initial content of microorganisms was about 10 7 The protein content was used as the benchmark to ensure that the initial concentration of the experimental group and the control group was consistent. The control group and the experimental group were cultured in a constant temperature shaking box at 30°C and 180 rpm, and the ferrous iron concentration was measured at 0, 6, 12, 24, 48, 72 and 96 hours of the reaction.

[0083] Figure 6 is the kinetic curve of Fe(II) generated by hydrochloric acid extraction in the reduction stage of Experimental Example 2. Figure 6 It can be seen that in the control group with only added bacteria, the reduction rate of ferrihydrite is slow, the content of ferrous iron extracted by hydrochloric acid tends to balance after 48 hours of reaction, and the content of ferrous iron extracted by hydrochloric acid is only 60.78 mg / L after 96 hours of reaction, accounting for only 30.39% of the total amount of ferrihydrite. In the test group with added carbon-based material 2, the reduction rate of ferrihydrite is fast, the content of ferrous iron extracted by hydrochloric acid tends to balance after 6 hours of reaction, and the content of ferrous iron extracted by hydrochloric acid is 65.07 mg / L after 96 hours of reaction, accounting for 32.54% of the total amount of ferrihydrite. The results of the kinetic experiment show that the reduction rate of ferrihydrite is significantly different in the test group with added carbon-based material 2 and the control group with only added bacterial solution, and carbon-based material 2 can effectively promote the reduction process of ferrihydrite.

[0084] Test Example 3

[0085] The rice pot experiment was carried out in a greenhouse, and the specific steps are as follows:

[0086] (1) Seedling cultivation: Select an appropriate amount of rice seeds (yellow rice seeds) that are plump and uniform in size, place them in a clean beaker and dry them at 42°C for 2-3 days, then wash them and add 30% H 2 O 2 Soak the seeds for 10 minutes for disinfection, rinse them several times with ultrapure water and clean them thoroughly; add a certain amount of nutrient solution for seedling cultivation, and after three weeks of hydroponic growth, select seedlings of uniform size for experiments;

[0087] (2) Soil flooding and seedling transplanting: Each single pot (25 cm in diameter and 35 cm in height) was filled with 5 kg of soil and 3 L of water, which was allowed to stabilize for 2-3 days. Then the seedlings were transplanted into the pots, with 5 seedlings in a group and 3 groups planted in each pot;

[0088] (3) Rice flooding stage: Flooding with deionized water under natural conditions, no fertilizer was applied during the period and the water depth in each pot was kept above 5 cm above the soil surface; 0.5 g of carbon-based material 1 was added to test group 1, and 0.5 g of carbon-based material 2 was added to test group 2. The concentration of carbon-based materials was about 0.1 g / kg, and the control group was not treated;

[0089] (4) Seven sampling points were set up according to the growth cycle of rice (seedling stage, tillering stage, jointing stage, booting stage, heading stage, flowering stage and filling and maturity stage). Soil samples and pore water solutions were collected on the 0th, 15th and 30th days of the flooding stage. A portion of the pore water solution was filtered with a 0.45 μm filter membrane and then used to determine the dissolved organic carbon content (DOC) in the soil using a total organic carbon analyzer. A portion of the pore water solution was filtered with a 0.22 μm filter membrane and then used to determine the content of water-soluble ferrous iron in the soil.

[0090] Figure 7 is the kinetic curve of Fe(II) extracted by hydrochloric acid in the reduction stage in Experimental Example 3, wherein: Figure 7 (a) is the kinetic curve of hydrochloric acid extraction of Fe(II) in the reduction stage of experimental group 1 and control group. Figure 7 (b) is the kinetic curve of hydrochloric acid extraction of Fe(II) in the reduction stage of experimental group 2 and control group. Figure 7 It can be seen that after 30 days of cultivation, the content of ferrous iron extracted by hydrochloric acid in the control group was only 1.74g / kg, while in the experimental groups 1 and 2 with the addition of carbon-based materials 1 and carbon-based materials 2, the content of ferrous iron extracted by hydrochloric acid was 5.74g / kg and 5.86g / kg respectively, indicating that carbon-based materials 1 and 2 can significantly promote the reduction and dissolution of iron minerals in the soil.

[0091] Figure 8 is the kinetic curve of DOC in the reduction stage in Experiment 3, where: Figure 8 (a) is the kinetic curve of DOC in the reduction phase of the experimental group 1 and the control group. Figure 8 (b) is the kinetic curve of DOC in the reduction phase of the experimental group 2 and the control group. Figure 8 It can be seen that after 30 days of cultivation, the content of dissolved organic carbon in the control group was 23.75 mg / L, while in the experimental groups 1 and 2 with the addition of carbon-based materials 1 and carbon-based materials 2, the content of dissolved organic carbon was 29.76 mg / L and 33.58 mg / L respectively, indicating that the addition of carbon-based materials can improve soil fertility and promote plant growth to a certain extent.

[0092] The carbon-based material provided by the present invention can effectively promote soil carbon fixation and the reduction and dissolution of minerals, realize the activation of mineral elements, and is beneficial to the absorption of mineral elements by crops. In addition to promoting the reduction and activation of iron elements in the soil, it also has great application potential for the activation of various mineral nutrients such as selenium, zinc, and calcium.

Claims

1. A carbon-based material, characterized in that: The carbon-based material is lignin modified by an electron shuttle.

2. The carbon-based material according to claim 1, characterized in that The mass ratio of the electron shuttle to lignin is 1: (0.5-25)。 3. The carbon-based material according to claim 2, characterized in that The electron shuttle is an anthraquinone compound; Preferably, the electron shuttle comprises anthraquinone-2-carboxylic acid.

4. The carbon-based material according to any one of claims 1 to 3, characterized in that: The carbon-based material comprises the following preparation raw materials: lignin, an electron shuttle, a solvent, a catalyst and a dehydrating agent.

5. The carbon-based material according to claim 4, characterized in that The mass ratio of the lignin, the catalyst and the dehydrating agent is 1000:(2-60):(40-800); Preferably, the catalyst comprises 4-dimethylaminopyridine; Preferably, the dehydrating agent comprises dicyclohexylcarbodiimide; Preferably, the solvent comprises a C1-C2 chloroalkane.

6. The method for preparing a carbon-based material according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1. Add lignin and electron shuttle into a reaction device, introduce inert gas, add solvent, and obtain a mixed solution; S2. Mix the catalyst, dehydrating agent and solvent, add them into the mixed liquid, react and obtain the carbon-based material.

7. The preparation method according to claim 6, characterized in that: In the step S1, the solid-liquid ratio of the lignin to the solvent is 1 g: (2-30) mL; And / or, in step S2, the solid-liquid ratio of the catalyst to the solvent is (0.2-10) mg:1 mL; And / or, in step S2, the reaction time is 24-96h.

8. Use of the carbon-based material according to any one of claims 1 to 5 in soil improvement.

9. The use according to claim 8, characterized in that: The soil improvement is to reduce and activate the mineral elements in the soil; Preferably, the mineral elements include iron, selenium, zinc and calcium.

10. The use according to claim 8 or 9, characterized in that: The amount of the carbon-based material used is (0.1-1.5) g / kg soil.

Citation Information

Patent Citations

  • Value-added urea capable of activating soil and preparation method thereof

    CN107082716A

  • Pretreatment of lignocellulosic material with anthraquinone salts in alkaline pulping

    CA986662A

  • Lignin-anthraquinone electrolyte material and preparation method and application thereof

    CN114989449A

  • Indigo whole-cell biological reduction dyeing method for wool

    CN116200954A

  • Method for reducing Cr (VI) through cooperation of bagasse lignin phenolic group and shewanella

    CN116768374A

Cited By

  • Slow-release phosphate fertilizer as well as preparation method and application thereof

    CN120117932A

  • Composite material as well as preparation method and application thereof

    CN121950323A